2018
DOI: 10.3892/ol.2018.8839
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiological features of lymphomatosis cerebri: A systematic review of the English literature with a new case report

Abstract: Lymphomatosis cerebri is a rare form of diffusely infiltrating primary central nervous system (CNS) lymphoma (PCNSL). The neuroradiological findings of lymphomatosis cerebri have not been adequately characterized, as the relevant literature consists only of case reports and small case series. The present study describes an unusual presentation of lymphomatosis cerebri in a 56-year-old immunocompetent woman who presented with diffusely infiltrating lesions with perivascular curvilinear enhancement on initial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…PCNSL lesions usually appear in the vicinity of the ventricle, and are often multiple. Initial symptoms may include subclinical intracranial pressure and psychiatric conditions in addition to other conditions originating in the brain such as paralysis and aphasia [ 5 ]. PCNSL with hypothalamic-pituitary lesions has been rarely reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCNSL lesions usually appear in the vicinity of the ventricle, and are often multiple. Initial symptoms may include subclinical intracranial pressure and psychiatric conditions in addition to other conditions originating in the brain such as paralysis and aphasia [ 5 ]. PCNSL with hypothalamic-pituitary lesions has been rarely reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2a ), we assume that the BBB might have been disrupted by the aggressive invasion of these cells, and that this disruption corresponded to the robust contrast enhancement on MRI. This differs from the non-contrast-enhancing lesions in typical LC, where diffusely infiltrative lymphoid cells do not affect the structure of the BBB ( 4 ).…”
Section: Discussionmentioning
confidence: 69%
“…Originally, the MRI features of LC were reported to consist of diffuse leukoencephalopathy in the cerebral hemispheres with no contrast enhancement, reflecting an intact blood-brain barrier (BBB) ( 2 ). However, subtle, patchy, or even mass-like enhanced lesions have been reported in the later stages of LC ( 4 - 7 ). A recent case series characterized the neuroradiological findings of LC and revealed that a relatively high percentage of patients (35.6%) demonstrated spreading of lymphoid cells along the corticospinal tracts ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On MRI, LC is characterized by diffuse, non-enhancing infiltrative lesions without mass formation or mass effect (1)(2)(3)(4)(5)(6)(7)(8)(9). The lesions of LC are likely to be most clearly demonstrated with a fluid-attenuated inversion recovery (FLAIR) sequence (2,3). The lesions also show a high signal intensity on diffusion-weighted imaging (DWI), and most of the lesions exhibit an increase in apparent diffusion coefficient (ADC) values on an ADC map (4), which may reflect the diffuse infiltration of non-cohesive malignant lymphoid cells (4).…”
Section: Introductionmentioning
confidence: 99%